Capital social y acción colectiva de la APAFA en la IEPPSE Padre Agustín Lopez Pardo 2023 - Raysky Rios, Ivan (2023)
The main objective of the study was to determine the relationship between social capital and the collective action of the APAFA in the IEPPSE Padre Agustín López Pardo in the year 2023. Applied research at a descriptive correlational level and developed through a non-experimental design, was taken as study sample to 251 parents, in addition, the data collection was carried out through the survey and recording the data in a questionnaire. Given this, the study concluded that the perception of parents about social capital is at a medium level, with a significant percentage that supports it. Regarding the perception of opportunity, motivation and ability, it is observed that parents have a medium level in these dimensions. Parents' evaluation of the development of collective action is mostly regular, with a considerable percentage supporting this perception. In relation to the management of resources, the majority evaluation was also regular. Regarding participation in activities, again a majority evaluation of regular is recorded. In short, a positive and significant correlation has been demonstrated between social capital and collective action; This is reinforced by the statistical correlation of 0.812, which has been contested as significant at the 0.000 level.